Genome-wide linkage and association mapping identify susceptibility alleles in ABCC4 for Kawasaki disease. Issue 7 (13th May 2011) - Khor, Chiea Chuen; Davila, Sonia; Shimizu, Chisato; Sheng, Stephanie; Matsubara, Tomoyo; Suzuki, Yasuo; Newburger, Jane W; Baker, Annette; Burgner, David; Breunis, Willemijn; Kuijpers, Taco; Wright, Victoria J; et al.
Abstract : Background: Kawasaki disease (KD) is a self limited vasculitis in which host genetics plays a prominent role. To further the understanding of the role of host genetics in KD, a three-stage genetic study was conducted that began with a family linkage study and ultimately involved more than 3000 individuals to identify new genetic contributions to KD susceptibility. Methods and results: A 26-family linkage study followed by fine mapping was performed in a cohort of 1284 KD subjects and their family members (total 3248 individuals). Suggestive evidence of disease linkage (logarithm of odds (LOD) ≥3.0, p<1.00×10 −4 ) was found for five genomic locations (Chr 3q, 4q, 10p, 13q, 21q). Two of these loci (Chr 4q and Chr 13q) overlapped with validated findings from a recent KD genome-wide association study. Fine mapping analysis revealed three single nucleotide polymorphisms (SNPs) in ATP-binding cassette, subfamily C, member 4 ( ABCC4 ) underlying the Chr 13q linkage peak showing evidence of association to KD (lowest p=8.82×10 −5 ; combined OR 2.00, 95% CI 1.41 to 2.83). ABCC4 is a multifunctional cyclic nucleotide transporter that stimulates the migratory capacity of dendritic cells. It is also a mediator of prostaglandin efflux from human cells and is inhibited by non-steroidal anti-inflammatory medications such as aspirin. Conclusion: These genetic data suggest that ABCC4 could play a fundamental role in KD pathogenesis with effects on immune activation and vascular response to injury.